2016
DOI: 10.5772/62975
|View full text |Cite
|
Sign up to set email alerts
|

Exosome Secretion — More Than Simple Waste Disposal? Implications for Physiology, Diagnostics and Therapeutics

Abstract: Less than 100 nm in size and spherical in form - exosomes – vesicles expelled and taken up by cells, have ignited a new-found fascination. One which is derived from the sheer variety of exosomal content, ranging from microRNAs to transcription factors, capable of affecting a multitude of processes and pathways simultaneously within a target cell. Initially dismissed in 1983 as a waste disposal mechanism, today they form an entire field of research, being documented thus far in invertebrates, mammals, pathogens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…The interphotoreceptor space is in constant contact with RPE microvilli, which are optimally positioned for phagocytic activities (Strauss, 2005). Increasing evidence suggests that various neurons shed vesicles as means of communication and to remove unwanted materials under neurodegenerative conditions (Nagarajah, 2016;Fowler, 2019). More recently, RPE cells have been reported to take up extracellular vesicles in an in vitro cell culture model (Nicholson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The interphotoreceptor space is in constant contact with RPE microvilli, which are optimally positioned for phagocytic activities (Strauss, 2005). Increasing evidence suggests that various neurons shed vesicles as means of communication and to remove unwanted materials under neurodegenerative conditions (Nagarajah, 2016;Fowler, 2019). More recently, RPE cells have been reported to take up extracellular vesicles in an in vitro cell culture model (Nicholson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, in recent years, it has been found that these tiny vesicles contain cell-specific proteins, nucleic acids and lipids, which can be transmitted to other cells as signaling molecules to change their functions. 24 Exosomes can play important roles in many physiological and pathological aspects, such as antigen presentation, growth and migration of tumors, repair of tissue damage, and so on. 25 In addition, exosomes secreted by different cells have unused components and functions, which can be used as biomarkers for disease diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, there was an extraordinary explosion of research in the field of sEVs. Circulating sEVs have gone from being considered as useless cellular metabolic waste disposal to play an important part in mediation of cell-to-cell communication [32,33]. In our study, as early as 7 days after SAVR, there was a marked increase of circulating sEVs before returning to initial values after 3 mo.…”
Section: Discussionmentioning
confidence: 45%